História do Museu Pedagógico Nacional: Pedagogium – um museu de grandes novidades (1890-1919) - Silva, Camila Marchi da (2021)
The National Pedagogic Museum – Pedagogium – was founded in 1890 and organized by Decree number 981, which foresaw the reform of primary and secondary education. It was the institution’s mission to offer the general public and mostly, teacher, the means to professional education, the exhibition of the best methods and most advanced educational material, as well as to provide different types of courses. For such, it was essential that the institution obliged by certain criteria: keep a permanent exhibit of the pedagogic museum; offer scientific courses; exhibit and put together science laboratories for physical sciences and natural history; organize annual school visitations; direct a model primary school; offer a class for manual crafts; organize collections and models for education in public schools; and publish an educational magazine. As such, this institution is also known for its history as a center for the education of teachers. However, its life as a museum for commercial exhibits is unknown. This work intends to, among other questions, understand and analyze the constitution of the Pedagogium’s collection, taking into consideration it’s relationships with commerce and industry, trying to comprehend its organization and, by hypothesis, identify and analyze commercial interference in the composition of said collection. The question is: what is the exact relationship of this institution, a symbol of educational modernity, with the educational industry and market of its time? In order to answer this question, research and analysis of documents and specialized bibliography was conducted at the National Archive, the Municipal Archive of Rio de Janeiro, the National Library and CEMI - Centro de Memoria Institutional, among other sources. It was observed that the Pedagogium worked, effectively, as a promotional museum, established relationships with companies that produced educational supplies and incentivized the use of materials, objects and educational technologies. Besides that, the institution’s role as providing education for teachers was confirmed, as it offered courses and conferences about several themes, being a space for research in the collection by teachers, promoting courses for the general public, as well as serving as a cultural center and space of debates and political disputes in the field of education. The National Pedagogic Museum can be understood as a museum for exhibits of innovation and pedagogic modernity - a grand museum of novelty